MODEL EKONOMI SWASEMBADA DAGING DI KABUPATEN ACEH BARAT - Sri Handayani; Maya Indra Rasyid (Universitas Teuku Umar, 2012)
Meat is a strategic commodity. West Aceh district has considerable potential for the development of cattle and buffalo farms, this is not independent of the support of local resources owned. The purpose of this research is to analyze the economic model of meat commodity in supporting self-sufficiency of meat in West Aceh. Data used in this research is secondary data year 2000-2016 (time series data). Analysis of the economic model of beef is done by the approach of econometric model, which is formulated in the form of simultaneous equations. Model estimation using two stage least squares (2SLS) method. The results show that the demand for meat in West Aceh is influenced by the price of beef, the price of beef, the price of chicken meat, the population and the income per capita. Beef production in West Aceh is influenced by the price of chicken meat, the price of beef, the price of buffalo meat, the population of cattle, the dummy of meat self-sufficiency and artificial insemination. The production of buffalo meat in West Aceh is influenced by the price of chicken meat, the price of beef, the price of the buffalo meat, the meat self-sufficiency dummy, the demand for meat, buffalo population and buffalo meat production in the previous year.